Characteristics and influencing factors of daily population flow in the Wuhan Metropolitan Region based on mobile signaling data - DENG Huilin, LIN Sainan (Ziyuan Kexue)
[Objective] As an important carrier of the flow of various factors, population flow plays an important role in enhancing the competitiveness of cities and promoting the integration of urban areas. From the perspective of districts and counties scale, it is of great significance to accurately grasp the micro-pattern and internal mechanism of population flow in the Wuhan Metropolitan Region for promoting regional integration and realizing high-quality regional development. [Methods] Taking the Wuhan Metropolitan Region as the research object and based on the mobile signaling big data, point of interest (POI) data and social and economic data in November 2020, the social network analysis method and quadratic assignment procedure (QAP) regression model were applied to analyze the temporal and spatial characteristics of daily population flow in the Wuhan Metropolitan Region at the districts and counties scale. The study also identified the structural characteristics of the population flow network and related influencing factors. [Results] (1) From a spatiotemporal perspective, population flows between districts and counties within the Wuhan Metropolitan Region demonstrate significantly higher frequency and intensity on weekdays compared to weekends. The daily population movement patterns are predominantly characterized by intra-city flows within individual prefecture-level cities, while simultaneously exhibiting multiple small-scale inter-city circulation loops across administrative boundaries. (2) The central and eastern districts and counties of the Wuhan Metropolitan Region frequently participated in the cross-regional population flow and social interaction, and played a core supporting role in the development and operation of the population flow network. (3) The barrier effect of administrative boundaries was most obvious in daily population movement, which is also affected by institutional and cultural barriers within the urban circle. Differences in per capita GDP, educational resources and medical services among counties were key factors that drove population mobility. [Conclusion] Districts and counties should take into account their own economic development characteristics and resource endowments to optimize resource allocation in urban areas from the aspects of breaking administrative barriers, increasing education and medical infrastructure, and stimulating economic vitality, in order to accelerate the integration process, reduce the phenomenon of “polarization”, and achieve high-quality regional development.